2007
DOI: 10.1248/bpb.30.428
|View full text |Cite
|
Sign up to set email alerts
|

Cochinin B, a Novel Ribosome-Inactivating Protein from the Seeds of Momordica cochinchinensis

Abstract: Ribosome-inactivating proteins (RIPs) are RNA N-glycosidase enzymes, which are isolated from seeds of many plants. RIPs remove a site-specifically single adenine residue (A 4324 in the case of rat liver ribosome) from the highly conserved sarcin/ricin loop of the 28S rRNA, thus arresting protein synthesis.1,2) RIPs are conventionally classified into three types: type I, II and III based on the conformation of their subunits.2) Type I RIPs are single-chained proteins with enzymatic activity and type II RIPs co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 20 publications
2
17
0
Order By: Relevance
“…In further studies, the biochemical and molecular analyses will be performed to explain additional mechanisms of how the MC could prevent such adverse effects. The protective tissue damage effect demonstrated in this study is a phytotherapeutic property of MC extract besides other pharmacological properties shown in previous reports (Zheng et al;Jung et al, 2013aJung et al, , 2013bLiu et al;Chuethong et al;Tien et al;Kang et al;Tsoi et al;Xiao et al, 2007Xiao et al, , 2009Rajput et al, 2007Rajput et al, , 2010. Moreover, MC extract indeed did not affect any male reproductive parameters including testicular histology as compared to the control.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In further studies, the biochemical and molecular analyses will be performed to explain additional mechanisms of how the MC could prevent such adverse effects. The protective tissue damage effect demonstrated in this study is a phytotherapeutic property of MC extract besides other pharmacological properties shown in previous reports (Zheng et al;Jung et al, 2013aJung et al, , 2013bLiu et al;Chuethong et al;Tien et al;Kang et al;Tsoi et al;Xiao et al, 2007Xiao et al, , 2009Rajput et al, 2007Rajput et al, , 2010. Moreover, MC extract indeed did not affect any male reproductive parameters including testicular histology as compared to the control.…”
Section: Discussionsupporting
confidence: 72%
“…Recently, various scientific studies have shown that MC fruit extract has antioxidant and pharmacological properties (Kubola & Siriamornpun, 2011). MC has been demonstrated to have anti-cancer activities (Zheng et al, 2014;Jung et al, 2013a;Liu et al, 2012;Chuethong et al, 2007;Tien et al, 2005). In addition, it was also reported for its anti-inflammatory effect (Jung et al, 2013b) and angiogenesis (Kang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This plant was identified to have various phytochemical components (Ishida et al, 2004;Kubola & Siriamornpun, 2011). These fruits have been reported to have antioxidant activity (Kubola & Siriamornpun), anti-inflammatory effect (Jung et al, 2013), immunomodulatory activity (Tsoi et al, 2006), antitumor properties (Chuethong et al, 2007), anti-cancer activity (Zheng et al, 2014;Petchsak & Sripanidkulchai, 2015). However, there was no report of the hypoglycemic effect of Gac aril (GA) on adverse male reproductive system in type-I DM animal model.…”
Section: Introductionmentioning
confidence: 99%
“…In traditional medicine, M. cochinchinensis is used to treat liver, stomach and kidney disorders, and it has detoxifying and antipyretic properties [9]. The anti-inflammatory, anti-oxidant, and antitumor activities of M. cochinchinensis have been demonstrated [11-13]. H. erectum is used to cure infectious disorders in traditional medicine, and it has antibacterial, antinociceptive and antipyretic properties [9].…”
Section: Introductionmentioning
confidence: 99%